Choroidal and Retinal Abnormalities by Optical Coherence Tomography in Endogenous Cushing’s Syndrome - Abalem, Maria Fernanda; Machado, Marcio Carlos; Santos, Helen Nazareth Veloso Dos; Garcia, Rafael; Helal, John; Carricondo, Pedro Carlos; Pimentel, Sérgio Luis Gianotti; Monteiro, Mario Luiz Ribeiro; Qian, Cynthia X.; Bronstein, Marcello Delano; Fragoso, Maria Cândida Villares Barisson (Frontiers in Endocrinology, 2016)
Context: Cortisol has been suggested as a risk factor for choroidal thickening, which may lead to retinal changes. Objective: To compare choroidal thickness measurements using optical coherence tomography (OCT) in patients with endogenous active Cushing’s syndrome and to evaluate the occurrence of retinal abnormalities in the same group of patients. Design: Cross-sectional study. Setting: Outpatient clinic. Patients: Eleven female patients with Cushing’s syndrome in hypercortisolism state as determined by the presence of at least two abnormal measurements from urinary cortisol 24h, no suppression of cortisol with low dose dexamethasone suppression test and nocturnal salivary cortisol levels and 12 healthy controls. Methods: Choroidal and retinal morphology was assessed using OCT. Main outcome measures: Choroidal thickness measurements and the presence of retinal changes. Results: The mean subfoveal choroidal thickness was 372.96 ± 73.14 μm in the patients with Cushing’s syndrome and 255.63 ± 50.70 μm in the control group, (p<0.001). One patient (9.09%) presented with central serous chorioretinopathy and one patient (9.09%) with pachychoroid pigment epitheliopathy. Conclusions: Choroidal thickness is increased in the eyes of patients with active Cushing’s syndrome compared to healthy and matched control. Also, 18.18% of patients presented with macular changes, possibly secondary to choroidal thickening. While further studies are necessary to confirm our findings excess corticosteroid levels seems to have a significant effect on the choroid and might be associated with secondary retinal diseases.